KAJIAN LITERATUR: PENGGUNAAN MODEL PEMBELAJARAN INOVATIF DALAM MENINGKATKAN HASIL BELAJAR IPS MATERI INTERAKSI MANUSIA DENGAN LINGKUNGAN DI KELAS V SD - Nuudiya Anburika; Luluk Lailatul Mukarromah; Eky Junnata Marianadya Sukadi; Desy Elvira Wulandari; Priyono Tri Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social Studies (IPS) learning in elementary schools still shows low student learning outcomes, particularly in the material on human interaction with the environment that requires conceptual and contextual understanding. This problem is caused by the dominant use of conventional teacher-centered learning, resulting in low student engagement. Although various innovative learning models have been widely researched, studies that integrate and compare their effectiveness specifically in elementary school social studies learning are still limited. This study aims to analyze and synthesize various innovative learning models and identify the most effective model in improving social studies learning outcomes. This study uses a qualitative approach with a literature review type. Data were obtained from relevant scientific articles and analyzed using content analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that innovative learning models such as Problem Based Learning (PBL), Project Based Learning (PjBL), cooperative models (TGT, STAD, Make A Match), Contextual Teaching and Learning (CTL), and Experiential Learning are consistently able to improve student learning outcomes. Problem-based and contextual models are considered the most effective because they are able to connect the material to students' real lives. Thus, selecting an innovative, adaptive, and contextual learning model is key to improving social studies learning outcomes.